China's ‘Singapore Model’ and Authoritarian Learning, 1st edition - Ortmann, Stephan (Routledge, 2020)
This book explores to what extent China has drawn lessons from Singapore, both in terms of its ruling ideology and through the policy-specific learning process. In so doing, it provides insights into the opportunities but also the challenges of this long-term learning process, focusing attention to how non-democratic regimes deal with modernization.